Structural changes in the mechanised fishing fleet of Kerala, South India - Ravi, Renju; Vipin, P.M.; Boopendranath, M.R.; Joshy, C.G.; Edwin, Leela (Indian Journal of Fisheries, 2014)
Kerala State situated in the south-west coast of India, has traditionally been the foremost fishery area of the Indian sub-continent. With increasing fishing pressure in the coastal waters, fishermen operating in mechanised sector were forced to venture in to deeper waters in search of newer fishing grounds in order to maintain their catches. Marine fisheries have undergone significant changes since the 1950s and the changes in number and capacities of fishing vessels have been more significant in the last decade. In this paper, an attempt has been made to compare the structural changes in terms of length overall (LOA) and installed engine horsepower among three commercially important fishing practices viz., trawling, purse seining and gillnetting in Kerala, over the last decade. The results have shown large scale changes in the structure of the fishing fleet in terms of size and installed engine horsepower among trawlers, purse seiners and gillnetters operating off Kerala. The study indicated an exponential growth in engine horsepower among trawlers above 18 m in LOA, in recent years. This paper also points out the need for regulating capacities of the fishing vessel in order to conserve fuel and reduce greenhouse gas (GHG) emissions.